Reworking the Brochure of Radya Pustaka Museum Surakarta: The Rhetorical One to Attract Locals - Bayu Budiharjo; Ida Kusuma Dewi; Dyah Ayu Nila Khrisna (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: Increasing tourists’ interest to visit museums can be accomplished through various promotional strategies. However, the Radya Pustaka Museum brochure falls short of successfully informing potential visitors about the museum's potency. Methodology: The brochure of Radya Pustaka Museum was first studied. Four locals were asked to review the brochure for naturalness and clarity. An open questionnaire was used, in which the respondents marked the expressions they perceived were unnatural or difficult to comprehend. In using content analysis, the primary data were gathered from the Indonesian descriptive texts in the brochure. Findings: Some of the information in the previous brochure of the Radya Pustaka museum was vague and confusing. Grammar mistakes, the frequent use of local cultural words, and overly complex sentences are all factors that contribute to this problem. To begin, all the grammatical errors and typos must be fixed. The museum's name should no longer be miswritten. Capitalization should also be considered when writing names and address forms. Additionally, each sentence must start with a subject. Conclusion: The proposed new concept brochure of the Radya Pustaka Museum in Surakarta is projected to increase the locals' interest in having a museum that they are eager to visit. The Appraisal theory was discovered to be useful in assisting the museum with these efforts because it is conceptually similar to rhetorical devices that effectively produce a promotional medium or message to engage the locals in embracing the museum. Originality: This study attempts to get the picture of the link between rhetorical strategies and Appraisal resources, as never been previously done, and make the best use of them to attract locals’ desire in visiting Radya Pustaka Museum. Due to the small number of studies looking into rhetorical tactics in brochures, this research also intends to fill the gap to shed more light on how the strategies can serve as valuable resources in making intended effects more impactful in communication using brochures.